Ossification of ligamentum flavum causing spinal stenosis: A case report - (:unkn) unknown (My University, 2008)
Ligamentum flavum ossifikasyonu çoğunlukla Japonlarda görülen nadir bir antitedir. Bu çalışmada, 46 yaşında erkek hastada torakal (Th) 2. vertebra seviyesinde bulunan ligamentum flavum ossifikasyonu ve buna eşlik eden servikal 5-6 disk hernisi bulunan bir olgu sunulmaktadır. Spinal kord basısına bağlı myelopatik semptomlarla başvuran hastaya Th 2 laminektomi uygulanmıştır. Ligamentum flavum ossifikasyonunun spinal kord basısına neden olduğu intraoperatif görülüp; yapılan örnekleme ile de tanı histopatolojik olarak desteklenmiştir. Sorunsuz bir ameliyat geçiren hastanın şikayet ve bulgularının dekompresif laminektomi sonrası belirgin şekilde gerilediği görülmüştür.

Ossification of the ligamentum flavum is a rare entity observed exclusively in Japanese people. We report a new case in a 46-year old man with ossification of the ligamentum flavum that was located at the thoracic (Th) 2 vertebra level with cervical disc herniation at the cervical (C) level 5-6. The patient showed myelopathy symptoms due to the compression on the spinal cord. A decompressive Th 2 laminectomy was performed. The cause of the compression was found to be an ossified ligamentum flavum, which was confirmed by histopathological examination. The postoperative course was uneventful and signs, symptoms, and functional status markedly improved after decompressive surgery.
Ligamentum flavum ossifikasyonuna bağlı spinal stenoz : Olgu sunumu
Keywords: Cerrahi